ADMINISTRATIVE SANCTIONS OF LICENCE VIOLATION IN THE FIELD OF PROTECTION AND ENVIRONMENTAL MANAGEMENT ON DISTRICT/ CITY IN CENTRAL JAVA PROVINCE - Endah Pujiastuti; Dewi Tuti Muryati (Faculty of Law, Universitas Jenderal Soedirman, 2018)
The Government of Indonesia has established policy to provide protection and environmental management. for the effectiveness of law enforcement, the government has a policy to supervise and give administrative sanction if there is a violation of licensing on the protection and management of the environment. This legal research analyzes policy on administrative sanctions against abuses of licensing protection and environmental management by using statute approach and qualitative analysis. Based on research result, it shows that the policy refers to the Law Number 32 of 2009 on the Protection and Environmental Management. For the implementation of the policy, it will be published in accordance with the needs of each region in the form of local regulations which includes the administrative sanctions in the field of environmental protection and management. Keywords: administrative sanctions, environment, local government.